The rhetorical situation of the COVID-19 public briefings on national response measures in Namibia (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
This paper analyses the rhetorical situation of the COVID-19 public briefings on national response measures in Namibia presented to the Namibian nation by the Namibian government. The rhetorical situation by Bitzer (1968) is a combination of people, events, objects, and contexts, as well as the nature in which specific discourse is created and how it shapes reality. The COVID-19 public briefing statements on the national response measures that Namibia had to follow during the different stages of COVID-19 established by the Namibian government are qualitatively analysed in this paper to describe the rhetorical situation during COVID-19 in Namibia. The analysis is based on Bitzer’s constituents of any rhetorical situation: the exigence, audience, constraints as well as the fitting response. While COVID-19 was presented as the exigence, the Namibian nation at large was the audience for whom the briefings were prepared. These statements were made through the media by the President and complemented by selected ministers. The media, which were always present at these briefings, were given a platform to ask questions on behalf of themselves and the nation, at times, presented as constraints.
Keywords: Rhetorical situation; COVID-19; Digital rhetoric; Information dissemination; Rhetorical discourse